COVID-19 pandemic lockdown: online platforms as panacea for effective teaching and learning in Nigerian secondary schools - Yunus, Aliyu; Abubakar, Saidu; Abudu, Zeinab Assake (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research is to examine online platforms as panacea for effective teaching and learning in Nigerian secondary schools during covid-19 pandemic lockdown. Three objectives were stated in this chapter by investigating the online platforms that are available to Nigerian secondary school students during COVID-19 pandemic lockdown, determine the accessibility of online platforms to secondary school students during COVID-19 pandemic lockdown in Nigeria and investigate the usefulness of online platforms among the Nigerian secondary school students during COVID-19 pandemic lockdown. Furthermore, descriptive statistics such as mean, standard deviation and percentage were used to analysed above objectives. It is shown that the majority of Nigerians secondary schools students disclosed that online platforms such as google, Decebo, Adobe, class-captive and among others are available for learning during Covid-19 pandemic lockdown. It is discovered from this finding that RCampus online platforms makes them have access to the learning discussions, assignments and video links with a mean of 3.70 or 91% among the ten items. Indisputably, the total mean of ten items 24.93 reveals that online platform assists and helps the learners in a useful and positive way during the outbreak lockdown in Nigeria. Similarly, the outcome of this result also agreed that students feel academically and socially integrated since they exposed to online platforms with a mean score of 3.50 between all the ten items. Thus, this study contributes significantly to Nigerian governments (Federal, State and Local) to direct all Nigeria secondary school students to be involved in internet and Information Communication Technology (ICT) with their subject teachers in order to ease academic activities between educators and leaners particularly in during critical condition like the plague situation the all globe is passing through.